Need help in this question asap srry i need points
Answer:
B 3
Step-by-step explanation:
We can use the secant-secant formula:
(whole secant) x (external part) =
(whole secant) x (external part)
9 * 4 = 12 *x
36 = 12x
Divide each side by 12
36/12 =12x/12
3 =x
The answer depends on whether you're looking for the x or the y. If y, the answers are the ones on the left, and the x on the right.
1) -4x + 3y ≤ 15 -4x + 3y <span>≤ 15
</span><span> +4x +4x -3y -3y
3y </span>≤ 4x + 15 -4x <span>≤ -3y + 15
</span><span> --- --------- ---- ------------
3 3 -4 -4
y </span>≤ 4/3x + 5 x <span>≥ 3/4y + 11
2) -6x - 4y </span>< 12 -6x - 4y < 12<span>
+6x +6x +4y +4y
-4y </span>< 6x +12 -6x < 4y + 12<span>
---- ---------- ---- -----------
-4 -4 -6 -6
y </span>> -3/2 - 3 x > -2/3y - 2
Answer:
Its the first option.
Step-by-step explanation:
3x + y = 5
5x - 4y = -3
From equation 1:
y = - 3x + 5
Substituting for y:
5x - 4(-3x + 5) = -3
The second one because 1/4 times 3/3 equals 3/12